Chlorine-free complex electrolyte for improving performance of magnesium battery and preparation method thereof

By combining sodium sulfate, sodium carbonate and 2-methylimidazole in the chlorine-free composite electrolyte, a dense protective layer is formed, which solves the problems of unstable voltage and low anode utilization efficiency during the discharge process of magnesium-air batteries and achieves efficient discharge performance improvement.

CN119581755BActive Publication Date: 2025-10-10NORTHEASTERN UNIV CHINA

Patent Information

Application Number
CN202510059357.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-10-10
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

During the discharge process of magnesium-air batteries, the magnesium anode reacts with the electrolyte to generate insoluble discharge products, resulting in unstable output voltage and power, low anode utilization efficiency, and existing electrolyte improvement methods are ineffective or have corrosion problems.

Method used

A chlorine-free composite electrolyte, including a mixed solution of sodium sulfate, sodium carbonate and 2-methylimidazole, was used. By adjusting the pH value to 7.0±0.2, a dense magnesium carbonate layer and chemical adsorption of 2-methylimidazole were formed, which inhibited the reaction of H+ with the magnesium matrix and avoided the deposition of insoluble products.

Benefits of technology

The discharge voltage of the magnesium-air battery has been significantly improved to -1.9V, the anode utilization efficiency has reached 87%, and the specific capacitance has been increased by 749.2mAh·g-1, meeting the requirements of low current density working conditions. It is low-cost and easy to configure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581755B_ABST
    Figure CN119581755B_ABST
Patent Text Reader

Abstract

The application discloses a chlorine-free compound electrolyte for improving magnesium battery performance and a preparation method thereof, and belongs to the technical field of magnesium air battery electrolytes.The chlorine-free compound electrolyte for improving magnesium battery performance is a mixed solution of sodium sulfate, sodium carbonate, 2-methyl imidazole and deionized water.The application first uses sodium sulfate to replace sodium chloride to avoid chlorine ions from accelerating magnesium corrosion;sodium carbonate reacts with a magnesium matrix to form a uniform thin magnesium carbonate layer;and 2-methyl imidazole uses a large Pi bond structure and nitrogen atoms to adsorb positive charge magnesium surfaces to form a dense film layer.The synergistic effect of the three materials can inhibit loose and porous discharge products from being deposited on the anode surface, greatly improve anode utilization efficiency to 87%, and improve the discharge voltage to -1.9 V.The application adjusts the ratio of a solvent to a solute to maximize the improvement of the discharge performance of the air battery;the prepared battery has the advantages of green environmental protection, convenient operation, simple preparation process and the like, and can realize the potential of remote electronic equipment application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium-air battery electrolytes, and particularly relates to a chlorine-free composite electrolyte for improving magnesium battery performance and a preparation method thereof. Background Art

[0002] At present, the shortage of fossil energy has become a serious problem faced by countries around the world. Magnesium-air batteries have obvious advantages over other air batteries. Although lithium-air batteries can be charged and discharged, they are prone to safety problems during use. At the same time, the cost of lithium is high and the theoretical specific capacitance is low. Although zinc-air batteries are safe and low in cost, the activity of zinc metal is poor and it is difficult to maintain a high output voltage. During the discharge process, a stable passivation film is formed on the surface of the aluminum electrode of the aluminum-air battery. This passivation film affects the continuous discharge process of the substrate, thereby increasing the potential of the aluminum electrode, resulting in a continuous decrease in the output voltage and power of the air battery. Compared with other air batteries, magnesium-air batteries have unique advantages. Magnesium metal has high electronegativity and high chemical activity. Magnesium has high theoretical capacity and voltage, is easy to process and prepare, and is safe to use. Therefore, magnesium-air batteries have become a new favorite among scientific researchers. Magnesium-air batteries can be used in many fields such as submarines, long-distance electronic communication equipment, and emergency rescue in the wild. But at the same time, magnesium-air batteries also have their own problems. Since the magnesium anode and the electrolyte need to be in constant contact during the discharge process, the magnesium anode and the H in the electrolyte are in direct contact with each other. + The cathode hydrogen evolution reaction occurs, generating insoluble discharge products such as Mg(OH)2. These insoluble discharge products will coat the surface of the magnesium anode, hindering the continuous contact between the anode and the electrolyte, thereby affecting the stability of the output voltage and output power. In addition, the cathode hydrogen evolution reaction will cause excessive corrosion of magnesium during the discharge process. The discharge products formed by excessive corrosion will contain some undissolved magnesium matrix. These magnesium matrices enter the electrolyte and dissolve without participating in the actual discharge charge transfer process, greatly reducing the anode utilization efficiency and specific capacitance, and shortening the service life of the magnesium-air battery.

[0003] Currently, the two main approaches to improving the discharge performance of magnesium-air batteries are treating the anode material and adjusting the chemical composition of the magnesium-air battery electrolyte. Generally speaking, methods for treating the anode material include alloying or heat treatment. Alloying treatments, such as adding elements like tin and calcium, inhibit the effects of impurities like iron and manganese on the magnesium matrix, reducing the potential difference between the matrix and the second phase, and improving the corrosion resistance of the magnesium during discharge. Heat treatments, such as low-temperature tempering, improve the content and distribution of the second phase in the alloy, promoting uniform dissolution of the anode during discharge and improving discharge performance. However, overall, alloying or heat treatment methods for improving the discharge performance of magnesium-air batteries require expensive processing equipment and are time-consuming. While these methods improve the discharge performance of the anode, the improvement is not significant. Compared to improving the anode, adjusting the electrolyte composition of magnesium-air batteries is simpler, less costly, greener, and more efficient. It can significantly inhibit corrosion during discharge, leading to overall improvements in discharge voltage and anode utilization efficiency. Therefore, adjusting the actual chemical composition of the magnesium-air battery electrolyte is of great significance for promoting the practical production and application of magnesium-air batteries.

[0004] At present, there are few inventions that improve the discharge performance of magnesium-air batteries by adjusting the chemical composition of the magnesium-air battery electrolyte, and they are worthy of in-depth study. Patent application number CN118610664A, "An electrolyte containing sodium dihydrogen phosphate additive and its application in magnesium-air batteries", proposes a mixture of disodium hydrogen phosphate and sodium acetate as the electrolyte of magnesium-air batteries. The invention shows the discharge voltage under three current densities. The invention shows that the discharge voltage of the anode is the highest in 0.005 mol / L sodium acetate and 0.5 mol / L sodium acetate. However, its anode discharge voltage is not stable. At the same time, the invention shows that the absolute value of the discharge voltage of the magnesium anode during the discharge process in this electrolyte is too low, only around 1.6V, which cannot meet the actual use process of the air battery. At the same time, the patent does not show the discharge performance of the magnesium anode under low current conditions. The discharge performance under low current density is of significant significance to magnesium-air batteries because magnesium-air batteries are mostly used in remote electronic devices, where the current density used is very low, about 0.4-0.6 mA·cm -2 .

[0005] The patent application number CN118472433A, "A method for preparing a 3-pyridinesulfonic acid magnesium air battery electrolyte", proposes an electrolyte composed of 0.01 mol / L corrosion inhibitor gadolinium chloride, 0.1 mol / L titanium iron reagent, and 0.6 mol / L sodium chloride to improve the performance of magnesium air batteries. This method can improve the corrosion resistance of magnesium alloys in solution. After compounding, it can reduce the excessive consumption of the magnesium matrix when the complexing agent titanium iron reagent is used alone. However, the addition of corrosion inhibitors reduces the anode dissolution rate, which is very unfavorable for improving discharge activity. The maximum discharge voltage is only 1.557V. At the same time, the addition of chlorine elements will definitely promote corrosion and reduce the utilization efficiency of the matrix. The results show that the electrolyte did not significantly improve the anode utilization efficiency. The anode utilization efficiency was only increased to 52.8%, which is far from meeting the actual engineering requirements. In addition, the current density used in the test of this patent is too high, which is 5mA·cm -2 , without considering the battery performance under low current density conditions. Summary of the Invention

[0006] The present invention aims at the pure magnesium anode material due to the reaction with H in the electrolyte. + The reaction causes severe corrosion, which greatly reduces the utilization efficiency; insoluble Mg(OH)2 is deposited on the anode surface, resulting in low discharge voltage and large fluctuations. The present invention provides a chlorine-free composite electrolyte for improving the performance of magnesium batteries and a preparation method thereof.

[0007] The present invention provides a chlorine-free composite electrolyte for improving the performance of a magnesium battery, specifically a mixed solution of sodium sulfate, sodium carbonate, 2-methylimidazole and deionized water.

[0008] Furthermore, the concentration of sodium sulfate in the electrolyte is 0.45-0.65 mol / L, the concentration of 2-methylimidazole is 0.0005-0.006 mol / L, the concentration of sodium carbonate is 0.0005-0.025 mol / L, and the pH is 7.0±0.2.

[0009] The present invention provides a method for preparing the chlorine-free composite electrolyte for improving the performance of magnesium batteries, and the specific steps are as follows:

[0010] (1) mixing sodium sulfate, sodium carbonate, and 2-methylimidazole to prepare a mixed material;

[0011] (2) adding deionized water to the mixed material, and then accelerating the stirring of the mixed material and liquid to form a uniform transparent solution;

[0012] (3) Using sodium hydroxide or dilute sulfuric acid to adjust the pH value of the solution obtained in step (2) to obtain the chlorine-free composite electrolyte for improving the performance of the magnesium battery.

[0013] Furthermore, in step (2), deionized water is introduced into the mixed material placed in the container using a drainage device consisting of a funnel and a 500 mL beaker, and the mixed liquid is slowly poured along the inner wall of the container while stirring.

[0014] Furthermore, in step (2), the stirring speed is 100-150 rpm.

[0015] Furthermore, in step (2), the mixture needs to be heated during the stirring process, and the heating temperature is 40-50°C.

[0016] Furthermore, in the step (3), the pH value of the prepared electrolyte is regulated by a pH-conductivity meter, and the pH value is 7.0±0.2.

[0017] The present invention also provides an application method of the chlorine-free composite electrolyte for improving the performance of magnesium batteries, specifically:

[0018] An external current is applied to the electrochemical workstation and the battery voltage change signal is collected. Pure magnesium is used as the anode material, and 15%-25% of the surface area of ​​the magnesium anode material is exposed in a chlorine-free composite electrolyte that improves the performance of the magnesium battery.

[0019] Furthermore, in the use method, the specific pure magnesium material of the magnesium anode has a tin content of 0.01wt.%-0.012wt.%, and an iron / manganese impurity content of less than 0.01wt.%.

[0020] Furthermore, in the method of use, the current density of the current is 0.3-3 mA·cm -2 .

[0021] Furthermore, in the method of use, the positive electrode material includes copper sheet, graphite powder and platinum mesh; and the air cathode is prepared by 500 MPa pressing and shearing treatment.

[0022] Beneficial effects of the present invention:

[0023] The chlorine-free composite electrolyte provided by the present invention improves the performance of magnesium batteries. It uses sodium sulfate instead of sodium chloride to avoid the continuous corrosion of the magnesium matrix by chloride ions. Sodium carbonate and 2-methylimidazole are used as additives. Adjusting the ratio of the two has achieved a significant improvement in the discharge voltage and anode utilization efficiency of magnesium-air batteries for the first time. The reaction of sodium carbonate with the magnesium matrix forms a thin magnesium carbonate layer. This layer reduces the H in the solution. +Continuous contact with the magnesium matrix prevents the formation of a thick Mg(OH)2 layer. Furthermore, the large electronegative π-bond groups formed by the benzene ring-like structure in the 2-methylimidazole molecule attract the positively charged magnesium matrix, further compacting the surface film and ensuring a thin and dense discharge product film. The chlorine-free composite electrolyte prepared by the present invention improves magnesium battery performance, achieving simultaneous improvements in both utilization efficiency and discharge voltage.

[0024] After discharge of pure magnesium in the chlorine-free composite electrolyte provided by the present invention to improve magnesium battery performance, the discharge voltage increased from -1.46V to -1.9V (close to the theoretical value), a significant increase of approximately 440mV. This indicates that the chlorine-free composite electrolyte for improving magnesium battery performance significantly increases the discharge voltage of the air battery. Furthermore, the potential during the discharge process was stable, with no significant fluctuations in the potential.

[0025] The chlorine-free composite electrolyte provided by the present invention for improving the performance of magnesium batteries greatly increases the utilization efficiency of magnesium anodes to 87%. The specific capacitance is greatly improved, which is about 749.2 mAh·g compared with NaCl solution. -1 .

[0026] The chlorine-free composite electrolyte for improving the performance of magnesium batteries provided by the present invention successfully and significantly improves the discharge performance of air batteries. It not only ensures a high discharge voltage, which is close to the theoretical voltage of magnesium-air batteries of 2.37V, but also achieves a high utilization efficiency of 87%, thus having great application potential.

[0027] The present invention prepares a chlorine-free composite electrolyte for improving the performance of magnesium batteries. Compared with previous inventions, it has the following advantages: sodium sulfate is used instead of sodium chloride to avoid the corrosion and dissolution problem of magnesium during discharge caused by adverse ions such as chlorine. At the same time, the precipitation film formation principle of the reaction between sodium carbonate and the magnesium matrix and the chemical adsorption principle of 2-methylimidazole and the magnesium anode are utilized to effectively avoid the formation of a loose and thick layer of discharge products. The combination of these three meets the application requirements of magnesium-air batteries under low current density conditions. This chlorine-free composite electrolyte for improving the performance of magnesium batteries is green, efficient, easy to configure, low-cost, and convenient and fast. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The molecular structure and atomic electronegativity diagram of 2-methylimidazole;

[0029] Figure 2 Impedance analysis diagram of pure magnesium anode after immersion for 24 hours in comparative example and embodiment of the present invention;

[0030] Figure 3Figures 2 and 3 are potentiodynamic polarization diagrams of the pure magnesium anode after immersion for 1, 24, 48, and 72 hours in the comparative example and the embodiment of the present invention; wherein, Figure (a) is the potentiodynamic polarization diagram of the pure magnesium anode in comparative example 1; Figure (b) is the potentiodynamic polarization diagram of the pure magnesium anode in embodiment 1; Figure (c) is the potentiodynamic polarization diagram of the pure magnesium anode in embodiment 2; and Figure (d) is the potentiodynamic polarization diagram of the pure magnesium anode in embodiment 3;

[0031] Figure 4 Graphs showing hydrogen evolution of the pure magnesium anode after immersion for 7 days in the comparative example and the embodiment of the present invention;

[0032] Figure 5 Graphs showing weight loss and pH changes of pure magnesium anodes after immersion for 7 days in the comparative example and the embodiments of the present invention; wherein, FIG (a) is a graph showing weight loss changes of the comparative example and embodiments 1-3, and FIG (b) is a graph showing pH changes of the comparative example and embodiments 1-3;

[0033] Figure 6 The discharge voltage curves of pure magnesium anodes at different current densities for 10 h are shown in the comparative example and the embodiment of the present invention. Figure (a) shows the discharge voltage curves at a current density of 0.5 mA·cm -2 The discharge voltage curve of the discharge under 10h, Figure (b) is 2.5mA·cm -2 Discharge voltage curve of 10h discharge under the condition of ;

[0034] Figure 7 For pure magnesium anode, 0.5 mA·cm in the comparative example and the embodiment -2 Surface and cross-sectional morphology after 10h discharge at current density; Figure (a) shows the pure magnesium anode at 0.5mA·cm in Comparative Example 1. -2 Surface morphology of the pure magnesium anode after discharge at a current density of 0.5 mA cm in Example 1; Figure (b) shows the surface morphology of the pure magnesium anode after discharge at a current density of 0.5 mA cm -2 Surface morphology of the pure magnesium anode after 10h discharge at a current density of 0.5mA·cm -2 Surface morphology after discharge at current density of 0.5 mA cm in Example 3. -2 Surface morphology after discharge at current density of 0.5 mA cm-1 for 10 h; Figure (e) shows the surface morphology of the pure magnesium anode in Comparative Example 1 at 0.5 mA cm-1. -2 Cross-sectional morphology after discharge at current density of 0.5 mA cm-1 for 10 h; Figure (f) shows the cross-sectional morphology of the pure magnesium anode in Example 1 at 0.5 mA cm-1. -2 Cross-sectional morphology after discharge at current density of 0.5 mA cm-1 for 10 h; Figure (g) shows the cross-sectional morphology of the pure magnesium anode in Example 2 at 0.5 mA cm-1. -2 Cross-sectional morphology after 10 h of discharge at a current density of 0.5 mA cm -2Cross-sectional morphology after discharge for 10 h at the current density. DETAILED DESCRIPTION

[0035] The following examples are provided to further illustrate the present invention. It is hereby pointed out that the following examples are only illustrative of the implementation methods of the present invention. Those skilled in the art may make non-essential and appropriate improvements to the implementation methods after becoming proficient in the operation. The implementation methods are not limited to the examples provided by the present invention.

[0036] The chlorine-free composite electrolytes for improving the performance of magnesium batteries prepared in Comparative Example 1 and Examples 1-9 were tested under the following conditions, and the results obtained were plotted in graphs and tables.

[0037] Pure magnesium was used as the anode of the air battery, and the electrolytes were those prepared in Comparative Example 1 and Examples 1-9. A Princeton electrochemical workstation was used to apply power to the magnesium anode material. The specific composition of the pure magnesium anode included ≥99.9 wt.% magnesium, 0.01 wt.%-0.012 wt.% tin, and ≤0.1 wt.% impurity elements such as manganese and iron. The applied current density was 0.5 mA·cm -2 and 2.5 mA·cm -2 The cathode material is prepared by 500MPa pressure treatment and shearing, and is composed of copper mesh, platinum sheet and graphite powder.

[0038] Before the experiment begins, the anode sample needs to be polished with sandpaper until the particle size is 2000. After polishing, spray it with alcohol and blow it dry, then cool it to room temperature. The pure magnesium anode material is placed in Example 1 for about 24 hours. The area exposed to the electrolyte in the impedance analysis test is about 1.5 cm 2 , set the test frequency to 10 -2 ~10 5 Hz, and the material impedance analysis diagram was obtained; the pure magnesium anode material was placed in the electrolyte for 1-72 hours, and the area exposed to the electrolyte in the potentiodynamic polarization test was about 1.5 cm 2 The scanning rate of the potentiodynamic polarization test was 1 mV s -1 The anodic scan starts at the open circuit potential and continues until the current density reaches 10 mA cm -2 The cathode scan starts at 300 mV below the open circuit potential and ends when the current density reaches 10 mA cm -2; the potentiodynamic polarization curves of the pure magnesium anode material in the electrolyte were obtained; the pure magnesium anode material was placed at room temperature for seven days in Example 1, the weight loss before and after calculation was calculated, and the hydrogen release amount during the soaking process and the pH change of the comparative example were recorded. At this time, the size of the pure magnesium anode material used was 10x10x3mm, and the seven-day hydrogen evolution change graph, weight loss graph and pH change graph were obtained. After the discharge was completed, the surface and cross-sectional morphology of the pure magnesium anode after 10h of discharge in Example 1 were observed, and the surface and cross-sectional morphology after discharge were obtained. The discharge current density was 0.5mA·cm -2 and 2.5mA·cm -2 , and the discharge test duration was 10h; the weight loss of the pure magnesium anode material after the discharge in the comparative example was recorded, and the anode utilization efficiency and specific capacitance were obtained.

[0039] Comparative Example 1

[0040] Deionized water was added to sodium chloride, and a 45mm rotor was used for stirring treatment at a stirring speed of 120rpm; the solution was monitored by a pH-conductivity meter until the pH value was 7.0±0.2; and the comparative electrolyte was prepared. The concentration of the comparative electrolyte was 0.6mol / L.

[0041] The impedance analysis graph after 24h of immersion is shown in Figure 2 ; the pure magnesium anode showed a small capacitive arc in the comparative example 1, and an inductive arc appeared in the 24h impedance graph, which represented that the pure magnesium anode had poor corrosion resistance in the comparative example, indicating that it dissolved quickly during the discharge process, which was not conducive to improving the anode utilization efficiency. As shown in Figure 3 , the anodic polarization curve of the pure magnesium anode was continuously delayed to the right with the extension of the immersion time, which represented that the corrosion rate of the pure magnesium anode in the comparative example 1 was continuously accelerated, indicating that the micro-electrode corrosion was serious, which might cause a large amount of discharge product accumulation and was not conducive to the continuous discharge process; Figure 4 It is indicated that the hydrogen evolution rate is the fastest during the 7-day test process of the pure magnesium anode in the comparative example 1, reaching 4.3mL·cm -2 , reflecting that the corrosion and dissolution problem is serious. Figure 5 It is indicated that the weight loss rate reaches 1.75mg·cm -2 ·d -1 , and the pH increases rapidly, reaching 10.3 in 7 days, indicating that the anode reacts more with H + in the comparative example 1, resulting in a significant increase in alkalinity in the comparative example 1. As shown in Figure 6 , the pure magnesium anode in the comparative example 1 has a discharge voltage of 0.5mA·cm -2The discharge voltage at this current density was only 1.46 V. As the current density increased, the voltage dropped more significantly, reaching only 1.4 V. This indicates that Comparative Example 1 cannot provide a good output voltage for the pure magnesium anode, hindering discharge performance. Table 1 shows the utilization efficiency and specific capacitance changes of the pure magnesium anode after discharge in Comparative Example 1. The low utilization efficiency and specific capacitance indicate poor discharge performance in Comparative Example 1.

[0042] The calculation formula of anode utilization efficiency is as follows:

[0043]

[0044] The specific capacitance calculation formula is as follows:

[0045]

[0046] The theoretical weight loss calculation formula is as follows:

[0047]

[0048] The actual weight loss calculation formula is as follows:

[0049] ΔW=ΔW theo +ΔW self-corr +ΔW chunk effect (4)

[0050] From formula (1-4), we can know that the actual utilization efficiency depends on the self-corrosion weight loss (ΔW self-corr ) and the amount of undissolved magnesium matrix encapsulated in the discharge products (ΔW chunk effect ), and compared with the theoretical weight loss (ΔW theo ) is irrelevant to this fixed value. Figure 4 The pure magnesium anode has the fastest hydrogen evolution rate in comparative example 1, and the mass of the magnesium matrix consumed by self-corrosion is the largest. Figure 7 The figure shows the content of discharge products on the surface and cross section of the pure magnesium anode after 10 hours of discharge. It was observed that a large amount of discharge products were deposited on the surface of the anode after discharge in Comparative Example 1, which significantly reduced the contact area between the anode and the electrolyte and was not conducive to increasing the discharge voltage, explaining the reason for the low discharge voltage of the anode in Comparative Example 1. At the same time, the cross-sectional view of the discharge products shows that after discharge in Comparative Example 1, there are many undissolved magnesium matrices. These magnesium matrices are dissolved in the solution without participating in charge transfer, greatly reducing the anode utilization efficiency and specific capacitance. In summary, the discharge voltage, utilization efficiency and specific capacitance of the pure magnesium anode in Comparative Example 1 were not improved.

[0051] Example 1

[0052] A chlorine-free composite electrolyte for improving the performance of a magnesium battery, comprising 0.45 mol / L sodium sulfate, 0.001 mol / L 2-methylimidazole, and 0.001 mol / L sodium carbonate.

[0053] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0054] The mixed material was stirred using a 45 mm rotor at a stirring speed of 150 rpm; the mixture was heated while stirring at 45° C., and the solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and the chlorine-free composite electrolyte for improving the performance of the magnesium battery described in Example 1 was prepared;

[0055] like Figure 2 As shown in FIG1 , the capacitive reactance arc of the pure magnesium anode material in Example 1 is large, and there are two obvious capacitive reactance arcs, indicating that the corrosion resistance of the anode is improved. This proves that compared with Comparative Example 1, the pure magnesium anode material in Example 1 has a larger charge transfer resistance and better corrosion resistance; the potentiodynamic polarization diagram of the pure magnesium anode material in Example 1 is shown in FIG1 . Figure 3 As shown in (b), the 24h anodic polarization curve shows a pseudo-passivation phenomenon, which indicates that the corrosion dissolution of the anode is inhibited and the corrosion resistance is improved. Figure 4 and Figure 5 The hydrogen evolution, weight loss, and pH changes of the pure magnesium anode material in Example 1 during the 7-day immersion process are shown. The hydrogen evolution of the pure magnesium anode in Example 1 is less than that in Comparative Example 1, which is 3.9 mL·cm -2 At the same time, the weight loss and pH change were also lower than those in Comparative Example 1, which were 0.47 mg·cm -2 ·d -1 and 10.2. This shows that H + The reaction with the magnesium matrix is ​​suppressed, and Example 1 helps to suppress the self-corrosion process of the magnesium anode. It should be noted that the three materials provided by the present invention have similar pH values ​​after being dissolved in water and do not cause large changes in pH and affect each other. Figure 1 The chemical structure of 2-methylimidazole and the electronegativity of each atom are shown. The benzene ring structure of 2-methylimidazole can form a large π bond with a negatively charged group. The first-principles calculations show that the electronegativity of the nitrogen atom on the benzene ring is -0.508, which can attract the positively charged magnesium matrix and cover it, thereby improving the corrosion resistance of magnesium. At the same time, the reaction equation of sodium carbonate and magnesium is 2NaCO3+Mg 2+ →MgCO3+2Na +It is known that MgCO3 is easier to deposit on the anode surface than Mg(OH)2, and the density of MgCO3 is significantly higher than that of loose Mg(OH)2, which helps to form a thin product layer to inhibit the deposition of loose corrosion products. In summary, sodium sulfate avoids the adverse effects of chloride ions, and the synergistic effect of 2-methylimidazole and sodium carbonate helps to form a thin, uniform and dense protective layer on the surface, inhibiting the H in the electrolyte. + This explains why Example 1 inhibits anode self-corrosion. Figure 6 As shown in Table 1, the discharge voltage of the pure magnesium anode material in Example 1 at two current densities is about 200 mV higher than that in Comparative Example 1, indicating that Example 1 effectively improves the discharge voltage. -2 Under the current density, the utilization efficiency is increased by about 11.2%, and the specific capacitance is increased by about 249.2mAh·g -1 ; 2.5mA·cm -2 At the current density, the utilization efficiency is increased by about 10%, and the specific capacitance is increased by about 230mAh·g -1 , which shows that Example 1 effectively improves the discharge performance of pure magnesium anode materials in electrolyte. At the same time, the surface and cross-sectional morphology after discharge found that the overall discharge product layer became thinner, which shows that Example 1 does help to change the morphology of the discharge product layer, effectively reducing the deposition of discharge products during the discharge process, facilitating continuous contact between the electrolyte and the pure magnesium anode material, and maintaining a high discharge voltage. At the same time, there is no obvious undissolved magnesium matrix, which shows that Example 1 also reduces the matrix consumption during the discharge process. Combined with Example 1, the self-corrosion behavior of the magnesium anode is suppressed, which explains why Example 1 improves the utilization efficiency and specific capacitance of the magnesium anode.

[0056] Example 2

[0057] A chlorine-free composite electrolyte for improving the performance of magnesium batteries, comprising 0.45 mol / L sodium sulfate, 0.003 mol / L 2-methylimidazole, and 0.005 mol / L sodium carbonate.

[0058] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0059] The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was simultaneously heated at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and Example 2 was prepared.

[0060] like Figure 2As shown in FIG1 , after immersion for 24 hours, the capacitive reactance arc of the pure magnesium anode material in Example 2 is significantly greater than that in Comparative Example 1, and no inductive reactance occurs, indicating that Example 2 improves the corrosion resistance of the anode material; the potentiodynamic polarization diagram of the pure magnesium anode material in Example 2 is shown in FIG1 . Figure 3 As shown in Figure 2, the anode polarization curve showed a passivation phenomenon at 48h, indicating that the dissolution process of the anode in Example 2 was inhibited. Compared with Comparative Example 1, Example 2 improved the anode corrosion resistance. After seven days of immersion, the amount of hydrogen evolution and weight loss were 3.9mL·cm -2 and 0.33 mg·cm -2 ·d -1 , pH changed to 10.2, which was lower than that of Comparative Example 1, which also proved that Example 2 effectively inhibited H + A large amount of self-corrosion and dissolution caused by reaction with the magnesium matrix. 0.5mA·cm -2 At this current density, after 10 hours of discharge, the absolute value of the discharge voltage of the pure magnesium anode reaches 1.8V, indicating that it increases the discharge voltage by about 300mV. Comparing the utilization efficiency and specific capacitance values ​​shown in Table 1, it is found that Example 2 has a high discharge voltage at 0.5mA·cm -2 Under the current density, the anode utilization efficiency and specific capacitance are effectively improved to 72.9% and 1650mA·h·g -1 As the current density increases, the battery performance can still be improved, 2.5mA·cm -2 Under the current density, the utilization efficiency is improved by about 15%. The changes in these indicators show that Example 2 effectively improves the discharge performance of the pure magnesium anode and effectively increases the service life of the anode material. The surface area cross-sectional morphology of the pure magnesium anode after discharge is as follows Figure 7 As shown, it was observed that a dense film layer was formed on the surface after discharge, corresponding to high utilization efficiency and specific capacitance.

[0061] Example 3

[0062] A chlorine-free composite electrolyte for improving the performance of magnesium batteries, comprising 0.5 mol / L sodium sulfate, 0.005 mol / L 2-methylimidazole, and 0.01 mol / L sodium carbonate.

[0063] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0064] The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was simultaneously heated at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and Example 3 was prepared.

[0065] like Figure 2As shown in the figure, the capacitive reactance arc of the pure magnesium material in Example 3 is the largest after immersion for 24 hours, which proves that the anode material in Example 3 has the best corrosion resistance. At the same time, after immersion for 96 hours, the anode polarization curve still shows obvious passivation phenomenon, which also shows that it is most helpful in inhibiting the self-corrosion phenomenon of the magnesium matrix. Figure 4-5 As shown in the figure, the amount of hydrogen released by the pure magnesium material after soaking for seven days in Example 3 is 2.5 mL·cm -2 The corresponding weight loss is only 0.26 mg·cm -2 ·d -1 , pH increased to 9.9. This shows that Example 3 inhibits the interaction between the magnesium anode and H in the electrolyte. + The reaction capacity is the strongest and the restriction on the self-corrosion behavior of magnesium anode is the best. -2 Under the current density, the absolute value of the discharge voltage is increased to 1.9V. Compared with Comparative Example 1, it is increased by about 400mV. It is known that the theoretical voltage of the magnesium anode is 2.3V. The absolute value of the potential reached by the pure magnesium anode material in Example 3 is close to the theoretical value, indicating that Example 3 has greatly improved the anode discharge performance. -2 Under the current density, the discharge voltage of Example 3 is still greatly improved by about 400mV, which shows that the discharge performance of the pure magnesium anode in Example 3 is stable and reliable. By observing the changes in utilization efficiency and specific capacitance value, it is found that the pure magnesium material in Example 3 is 0.5mA·cm -2 The anode utilization efficiency and specific capacitance are 87% and 1960 mAh g-1 respectively at the current density. -1 2.5mA·cm -2 Under the current density, the utilization efficiency is still 80%, which fully meets the actual production and living needs. Example 3 significantly improves the discharge performance of the pure magnesium anode. The surface area cross-sectional morphology after discharge is as follows Figure 7 (d) and Figure 7 As shown in (h), it was observed that the pure magnesium anode material formed a dense, uniform and thin discharge product layer with a thickness of 2 microns after discharge in Example 3. This layer not only effectively suppressed the H + The unfavorable hydrogen evolution reaction with the magnesium matrix reduces the self-corrosion rate and improves the anode utilization efficiency, and avoids the formation of a thick discharge product layer that affects the charge transfer process, thereby greatly increasing the discharge voltage, which ultimately determines that the pure magnesium anode material exhibits excellent discharge performance in Example 3.

[0066] Example 4

[0067] A chlorine-free composite electrolyte for improving the performance of magnesium batteries, comprising 0.5 mol / L sodium sulfate, 0.0045 mol / L 2-methylimidazole, and 0.015 mol / L sodium carbonate.

[0068] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0069] The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was simultaneously heated at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and Example 4 was prepared.

[0070] like Figure 6 As shown in Table 1, 0.5 mA·cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 4 was increased to 1.81 V. -2 At this current density, the discharge voltage is increased to 1.72V, which is significantly higher than the voltage shown in Comparative Example 1. At the same time, the anode utilization efficiency and specific capacitance are also greatly improved, 0.5mA·cm -2 At the current density, they reached 84% and 1897.5 mAh g -1 ; When the current density increases, 2.5mA·cm -2 At the current density, they reached 70.6% and 1594.8 mAh g -1 The pure magnesium anode material exhibited good discharge performance in Example 4.

[0071] Example 5

[0072] A chlorine-free composite electrolyte for improving the performance of magnesium batteries, comprising 0.55 mol / L sodium sulfate, 0.0045 mol / L 2-methylimidazole, and 0.02 mol / L sodium carbonate.

[0073] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0074] The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was simultaneously heated at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and Example 5 was prepared.

[0075] Figure 6 Table 1 summarizes the discharge performance of the magnesium anode in Example 5, 0.5 mA·cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 5 was increased to 1.72 V. -2 At this current density, the discharge voltage increased to 1.68 V, which is significantly higher than the voltage shown in Comparative Example 1. At the same time, by comparing the anode utilization efficiency and specific capacitance value, it was found that 0.5 mA cm -2 At the current density, they reached 73.2% and 1653.6 mAh g -1; When the current density increases, 2.5mA·cm -2 At the current density, they reached 68.4% and 1545.1 mAh·g -1 The pure magnesium anode material in Example 5 exhibits high discharge performance at various current densities.

[0076] Example 6

[0077] A chlorine-free composite electrolyte for improving the performance of magnesium batteries, comprising 0.55 mol / L sodium sulfate, 0.005 mol / L 2-methylimidazole, and 0.02 mol / L sodium carbonate.

[0078] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0079] The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was simultaneously heated at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and Example 6 was prepared.

[0080] The discharge performance of the magnesium anode in Example 6 is also higher than that in Comparative Example 1, 0.5 mA·cm -2 At the current density of 2.5 mA cm, the discharge voltage of the pure magnesium anode in Example 6 was increased to 1.7 V, which was about 240 mV higher than that in Comparative Example 1. -2 At this current density, the discharge voltage increased to 1.66 V. It was also found that 0.5 mA cm -2 At the current density, the anode utilization efficiency and specific capacitance reached 70.2% and 1585.8 mAh g, respectively. -1 ; The current density increased to 2.5 mA·cm -2 When the temperature is high, it reaches 66.6% and 1504.5mAh·g respectively. -1 .

[0081] Example 7

[0082] A chlorine-free composite electrolyte for improving the performance of magnesium batteries, comprising 0.6 mol / L sodium sulfate, 0.0055 mol / L 2-methylimidazole, and 0.02 mol / L sodium carbonate.

[0083] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0084] The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was simultaneously heated at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and Example 7 was prepared.

[0085] The discharge performance of the magnesium anode material in Example 7 is as follows: Figure 6 As shown in Table 1, 0.5 mA·cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 7 was increased to 1.68 V. -2 At this current density, the discharge voltage increased to 1.64 V, which is higher than the voltage shown in Comparative Example 1. At the same time, by comparing the anode utilization efficiency and specific capacitance value, it was found that 0.5 mA cm -2 At the current density, they reached 66.2% and 1495.4 mAh g -1 ; 2.5mA·cm -2 At the current density, they reached 65.2% and 1472.8 mAh g -1 The pure magnesium anode material in Example 7 showed good discharge performance.

[0086] Example 8

[0087] A chlorine-free composite electrolyte for improving the performance of magnesium batteries, comprising 0.6 mol / L sodium sulfate, 0.0055 mol / L 2-methylimidazole, and 0.025 mol / L sodium carbonate.

[0088] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0089] The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was simultaneously heated at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and Example 8 was prepared.

[0090] Compared with Comparative Example 1, the discharge performance of the magnesium anode in Example 8 is improved, 0.5 mA·cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 6 was increased to 1.66 V, which was about 200 mV higher than that in Comparative Example 1. -2 At this current density, the discharge voltage increased to 1.63 V. It was also found that 0.5 mA·cm -2 At the current density, the anode utilization efficiency and specific capacitance reached 65.9% and 1488.7 mAh g, respectively. -1 ; The current density increased to 2.5 mA·cm -2 When the temperature is high, it reaches 64.1% and 1447.9 mAh g -1 .

[0091] Example 9

[0092] A chlorine-free composite electrolyte for improving the performance of magnesium batteries, comprising 0.65 mol / L sodium sulfate, 0.006 mol / L 2-methylimidazole, and 0.0025 mol / L sodium carbonate.

[0093] Mixing sodium sulfate, 2-methylimidazole and sodium carbonate to prepare a mixed material;

[0094] The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; the stirring was simultaneously heated at a heating temperature of 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2; and Example 9 was prepared.

[0095] The discharge performance of the magnesium anode in Example 9 is still better than that in Comparative Example 1, 0.5 mA·cm -2 At the current density of 2.5 mA·cm, the discharge voltage of the pure magnesium anode in Example 6 was increased to 1.65 V; at 2.5 mA·cm -2 At this current density, the discharge voltage increased to 1.63 V. It was also found that 0.5 mA·cm -2 At the current density, the anode utilization efficiency and specific capacitance reached 62.2% and 1405 mAh g respectively. -1 ; The current density increased to 2.5 mA·cm -2 When the temperature reaches 60.3% and 1362.2 mAh g -1 .

[0096] Table 1 Current density is 0.5 mA·cm -2 The utilization efficiency and specific capacitance of pure magnesium anode in comparative example and embodiment are shown in FIG.

[0097] Utilization efficiency (%) <![CDATA[比电容量(mAh·g -1 )]]> Comparative Example 1 53.6±1.2 1210.8±13.5 Example 1 64.8±3 1460±33.5 Example 2 72.9±1.4 1650.8±31.6 Example 3 87±1.7 1960±38.4 Example 4 84±1.7 1897.5±38.4 Example 5 73.2±1.5 1653.6±33.9 Example 6 70.2±1.3 1585.8±29.4 Example 7 66.2±1.5 1495.4±33.9 Example 8 65.9±0.7 1488.7±15.8 Example 9 62.2±0.5 1405±11.3

[0098] Table 2 Current density is 2.5 mA·cm -2 The utilization efficiency and specific capacitance of pure magnesium anode in comparative example and embodiment are shown in FIG.

[0099]

[0100]

Claims

1. A chlorine-free composite electrolyte for improving the performance of magnesium batteries, characterized in that: The chlorine-free composite electrolyte for improving the performance of magnesium batteries is a mixed solution of sodium sulfate, sodium carbonate, 2-methylimidazole and deionized water; the concentration of sodium sulfate is 0.45-0.65 mol / L, the concentration of 2-methylimidazole is 0.001-0.006 mol / L, the concentration of sodium carbonate is 0.001-0.025 mol / L, and the pH of the electrolyte is 7.0±0.

2.

2. The method for preparing the chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 1, characterized in that: The following steps are involved: (1) Mixing sodium sulfate, sodium carbonate, and 2-methylimidazole to prepare a mixed material; (2) Deionized water is added to the mixed material, and then the mixed material and liquid are accelerated to form a uniform transparent solution; (3) Using sodium hydroxide or dilute sulfuric acid to adjust the pH value of the solution obtained in step (2) to obtain a chlorine-free composite electrolyte that improves the performance of the magnesium battery.

3. The method for preparing a chlorine-free composite electrolyte for improving magnesium battery performance according to claim 2, wherein: In the step (2), deionized water is introduced into the mixed material placed in the container using a drainage device consisting of a funnel and a 500 mL beaker. The deionized water is slowly poured along the inner wall of the container while stirring.

4. The method for preparing a chlorine-free composite electrolyte for improving magnesium battery performance according to claim 2, wherein: In the step (2), the stirring speed is 100-150 rpm.

5. The method for preparing a chlorine-free composite electrolyte for improving magnesium battery performance according to claim 2, wherein: In the step (2), the heating state needs to be maintained during the stirring process, and the heating temperature is 40-50°C.

6. The method for preparing a chlorine-free composite electrolyte for improving magnesium battery performance according to claim 2, characterized in that: The pH value of the prepared electrolyte was regulated by a pH-conductivity meter, and the pH value was 7.0±0.

2.

7. The use of the chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 1, characterized in that: The application method is: applying an external current to an electrochemical workstation and collecting the battery voltage change signal, using pure magnesium as the anode material, and 15%-25% of the surface area of ​​the magnesium anode material is exposed to the electrolyte that improves the discharge performance of the magnesium anode material.

8. The use of the chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 7, characterized in that: In the application method, the magnesium anode material has a specific composition including ≥99.9 wt.% magnesium, 0.01 wt.%-0.012 wt.% tin, and contains impurity iron / manganese with a content of less than 0.01 wt.%.

9. The use of the chlorine-free composite electrolyte for improving the performance of magnesium batteries according to claim 7, characterized in that: In the application method, the current density of the energized current is 0.3-3 mA·cm -2 ; The positive electrode material includes copper sheet, graphite powder and platinum mesh, which is made by 500MPa pressing and shearing treatment.

Citation Information

Patent Citations

  • Preparation method of 3-pyridine sulfonic acid magnesium air battery electrolyte

    CN118472433A

  • Electrolyte containing sodium dihydrogen phosphate additive and application of electrolyte in magnesium air battery

    CN118610664A

  • Magnesium air battery electrode, magnesium air battery, aromatic compound, and metal complex

    CN108140920A

  • Electrolyte

    CN114631216A

Cited By

  • A magnesium battery with strong oxidant electrolyte

    CN122436625A